Response of nitrogen fertilizer and legumes residues on biomass production and utilization in rice-legumes rotation - Rahman, M.M.; Sofian-Azirun, Mohd; Boyce, A.N. (2013)
A cropping sequence including rice after winged bean, rice after bush bean, rice after corn, and rice after fallow with varying rates of nitrogen (N) fertilizer were carried out to investigate the effects of legume residues and N fertilizer to clarify dynamics of soil N supply, N utilization in soil-plant system and grain yield of rice. Nitrogen fertilizer was applied in both legumes at rates of 0, 2, 4 and 6 g m(-2). The first crop cycle for rice and corn were fertilized with N fertilizer at rates of 0, 4, 8 and 12 g m(-2) with no chemical fertilizer applied in the 2nd crop cycle for the legumes, corn and rice. In 2010, bush bean and winged bean accumulated 5.0-5.9 and 6.2-6.8 g N m(-2) of which 10.0-29.4 and 21.7-42.1 was derived from N-2 fixation. In 2011, bush bean and winged bean accumulated 4.7-5.6 and 5.8-6.9 g N m(-2) of which 13.2-28.8 and 29.5-41.4 was derived from N-2 fixation and estimated by total N difference method. Higher yield was recorded by rice after winged bean with N at rates of 4, 8 and 12 g N m(-2) during both years. This superior performance of rice after winged bean is likely linked to greater N fixation (21.7-42.1) and N uptake by both legumes. Such tropical legumes that improve productivity of rice might be attractive to farmers who are generally resource-poor farmers. The results revealed that bush bean and winged bean can supply >50 and >95 of N required for rice and can be a viable alternative organic N source to enhance soil fertility and reduce cost.